2019
DOI: 10.1097/md.0000000000016636
|View full text |Cite
|
Sign up to set email alerts
|

ECG pre-hospital teletransmission by emergency teams staffed with an emergency physician and paramedics and its impact on transportation and hospital admission

Abstract: Electrocardiography (ECG) is essential to detect and diagnose life threatening cardiac conditions and to determine further treatment. Correct interpretation of an ECG can be challenging, especially in the out-of-hospital setting and by less experienced emergency team members. The aim of this study was to compare the rate of ECG transmission from an out-of-hospital emergency scene to an in-hospital cardiologist on call in EMS-B and EMS-S providers and its impact on direct transportation to a cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The application of mobile technologies for health practice led to the significant improvement of early diagnostic and timely treatment of life-threating conditions such as cardiac arrest ( 113 - 118 ). In fact, early cardiopulmonary resuscitation and defibrillation using digital technologies could help safe many lives.…”
Section: Discussionmentioning
confidence: 99%
“…The application of mobile technologies for health practice led to the significant improvement of early diagnostic and timely treatment of life-threating conditions such as cardiac arrest ( 113 - 118 ). In fact, early cardiopulmonary resuscitation and defibrillation using digital technologies could help safe many lives.…”
Section: Discussionmentioning
confidence: 99%
“…ECG interpretation is often poor at the undergraduate and graduate levels [30]. Early detection and rapid revascularization of STEMI is essential and potentially life-saving [31]. The quick and correct diagnosis and interpretation of myocardial infarction can signi cantly reduce the door-to-balloon time for reperfusion [32].…”
Section: Discussionmentioning
confidence: 99%
“…This may be justi ed by the fact that the staff and students of nursing, anesthesiology and EMS do not have to interpret ECGs on a daily basis, unlike medical practitioners and students. Also, medical practitioners and students receive more personal training and expertise in ECG interpretation [2,31]. This is a warning sign for healthcare policymakers, who need to plan and implement useful measures to train paramedics in ECG interpretation and ensure they are specialized in this task.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Los Angeles found that among those diagnosed with ST-segment elevation myocardial infarction (STEMI) by P12ECG, only 28% had their data transmitted to the hospital; in 55% of cases, the data were not transmitted and for 17% of these cases the transmission status was not recorded [9]. In another study performed in Poland, 12-lead ECG was transmitted to the hospital by an emergency medical service (EMS) team for only 2% of patients [10].…”
Section: Prehospital 12-lead Electrocardiogrammentioning
confidence: 99%